GAMBARAN FARMAKOTERAPI DIARE AKUT PADA ANAK DI PUSKESMAS SIMPANG TIGA KOTA PEKANBARU PERIODE 1 JANUARI – 31 DESEMBER 2015 - Pertiwi, Lia; Nugraha, Dimas Pramita; ", Inayah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTDiarrhea is one of the major causes of infant and child death in Indonesia, so appropriate pharmacotherapy is needed. Acute diarrhea occurs less than fourteen days (two weeks). The aim of this study was to observe the description of pharmacotherapy diarrhea acute among children in Puskesmas Simpang Tiga Pekanbaru City from January 1st - December 31st 2015. This was a descriptive study using data from medical records. There were 147 samples that fulfilled the inclusion criterias. Acute diarrhea was most common found in male (61,9%). Age group of 1-5 years was the most common age group in this study (77,6%). Enough weight group was the common weight group in this study (80,3%), and oralit was the most used pharmacotherapy (74,8%). The appropriate zinc duration by WHOs standar in this study was 65,3%,and appropriate zinc frequency was 68,7%.Key words: acute diarrhea,pharmacotherapy